2004
DOI: 10.1093/jis/4.1.23
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the insecticide dichlorvos on esterase activity extracted from the psocids, Liposcelis bostrychophila and L. entomophila

Abstract: The inhibition kinetics of dichlorvos on carboxylesterase and acetylcholinesterase (AChE) activity extracted from Liposcelis bostrychophila and L. entomophila (Psocoptera: Liposcelididae) were compared. The results showed that L. entomophila had significantly greater specific activity of carboxylesterase than L. bostrychophila (0.045 versus 0.012 µmoles /mg /min). Moreover, the carboxylexterase of L. entomophila showed higher affinity (i.e. lower Km value) to the substrate 1-naphthyl acetate than L. bostrychop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 21 publications
1
11
0
1
Order By: Relevance
“…These enzymes are playing a vital role in insect pests; especially, the esterase family is helped in digestion, reproduction and metabolism of juvenile hormone, metamorphosis and detoxification of toxic substances [12,13]. Among the various enzymes in esterase families, one of the enzyme called acetylcholinesterase is present at nerve synapses and it helps to transmission of nerve impulse by hydrolysis of acetylcholine [14]. Carboxylesterase, is another important enzyme that plays a vital role in degradation of neurotransmitter, metabolism of specific hormones and pheromones, consequently involved in insect development and behavior, detoxification of toxic substances etc.…”
Section: Introductionmentioning
confidence: 99%
“…These enzymes are playing a vital role in insect pests; especially, the esterase family is helped in digestion, reproduction and metabolism of juvenile hormone, metamorphosis and detoxification of toxic substances [12,13]. Among the various enzymes in esterase families, one of the enzyme called acetylcholinesterase is present at nerve synapses and it helps to transmission of nerve impulse by hydrolysis of acetylcholine [14]. Carboxylesterase, is another important enzyme that plays a vital role in degradation of neurotransmitter, metabolism of specific hormones and pheromones, consequently involved in insect development and behavior, detoxification of toxic substances etc.…”
Section: Introductionmentioning
confidence: 99%
“…The infection mechanism of Beauveria in the host insects has been reported (Roberts et al 2004; Wang et al 2004; Thomas et al 2007). The primary route of host invasion is through the external integument via the attachment of the conidia to the cuticle, germination, followed by penetration into the cuticle.…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptome studies showed that P450s, GSTs, and ESTs may play a role in insecticide tolerance after short-term exposure to deltamethrin and malathion (Dou et al, 2013). Also enhanced carboxylesterase activities may contribute to insecticide tolerance or resistance in booklice (Wang et al, 2004). Elevated GST activities were also confirmed in DDVP and PH 3 -resistant strains of L. bostrychohila by enzymatic assays (Dou et al, 2009).…”
Section: Introductionmentioning
confidence: 94%